Methodological Issues of Using Interactive Educational Technologies in the Professional Training of Future Teachers of Russian Language and Literature (Journal of Educational Sciences, 2019)
The article is devoted to the methodological issues of introducing interactive forms of education – one of the most important areas for improving the preparation of students in a modern university. The authors emphasize that the modern possibilities of interactive teaching aids are the dominant of activity-based orientation of the student’s educational process at the university. Considering the educational process of the University as a complex system, including as the main components of professional training of the future pedagogue educating and shaping the activities of lecturers and educational and cognitive activity of students, the authors identify the following types (stages) of educational activity: (1) empirical activity as a stage of perception – the use of psychological and equipment specific approaches, aimed at attracting the attention of the student to the analyzed linguistic phenomenon; (2) heuristic activity to recognize the situation; (3) reproductive activities to transform the model and acquire new knowledge; (4) practical activities related to the development of skills. According to them, the authors have developed a training program with tasks, focusing on these stages. Prior to the application of the developed methodology, a questionnaire was conducted to identify the level of professional learning (students’ ability to self-study, the ability to attract new information on additional examples, the method of “display”, interactive learning with the assessment of the actions of students), evaluation of cognitive motivation and communicative activity of students. It was found that 46% of the students in the sample had a high level of professional learning, 44% above average, 7% average and 3% - reduced.Key words: interactive educational technologies, didactics, tool, multimedia.